A quick read of the CIETAC arbitration rules 2015. (8th September 2015) - Tao, Jingzhou; Zhong, Mariana
Abstract: The China International Economic and Trade Arbitration Commission (CIETAC) Arbitration Rules 2015 feature several significant changes focusing on improving the arbitration efficiency, adopting specially tailored rules for arbitrations in Hong Kong SAR, providing for pre-arbitration remedies to parties and adjusting organizational structure of CIETAC. These changes reflect the improvement of CIETAC's practice towards the current trend of international arbitration practice, provide arbitration practitioners in Hong Kong another option in choosing arbitration institution, and in the meantime, indicate CIETAC's position in coping with the post-CIETAC Split situation.